An audit to assess the quality of necropsies performed on stillborn infants. Issue 1 (27th December 2004) - Burnley, H; Moore, I
Abstract : Aims: To determine the quality of stillbirth postmortem reports and their contribution to a final diagnosis following the introduction of explicit consent forms after the Alder Hey inquiry. Methods: Necropsy reports from 100 consecutive stillbirths were reviewed from 2001 onwards. A spreadsheet compiled data items that were considered essential in the Royal College of Pathologists guidelines. The type of consent (with permission for organs/tissue retention) was recorded to assess the impact on establishing a cause of death. Results: Consent for tissue retention was obtained in 95 cases, whereas consent for organ retention was significantly lower (52 cases). In two cases, permission was refused for tissue retention and three requested external examinations only. Of these five, four had an undetermined cause of death, compared with 35 of 95 cases where permission for tissue retention was granted. All data items considered essential were recorded in every report. In 65 cases, the necropsy provided useful information, helped clinical care, and addressed parental concerns. Conclusions: There was no major impact of the type of necropsy consent on establishing a cause of death, apart from the case of limited necropsies without histological examination of tissue samples.